Towards functional safety and security for adaptive and flexible business processes. Issue 5 (1st May 2018) - Geist, Verena; Natschläger, Christine; Illibauer, Christa; Schewe, Klaus‐Dieter
Abstract: Business process management (BPM) provides many benefits for a company including productivity, efficiency, compliance, risk management, consistency, repeatability, and measurability. Many of these aspects also ensure and improve functional safety, privacy, and security in process execution. However, managed business processes lack flexibility; ie, changing a business process requires more effort than ad hoc execution and adaptation. Thus, especially in small companies, the acceptance rate of managed business processes is low. So we claim that in current BPM approaches, the structuredness ensuring functional safety and security concepts contradicts with the objective for flexibility. The main goal of the AdaBPM project is to address this contradiction by providing a formal approach to handle advanced adaptations and exception handling in business processes. The technical objectives of the project include (1) the definition of a basic framework being capable of handling different levels of adaptivity and considering security and safety requirements at the same time, (2) a rigorous process specification language and model refinement methods, (3) static business process adaptations, and (4) dynamic (or ad hoc) adaptations. The result of our research is a general approach for flexible BPM combined with the possibility to nevertheless manage the process and define safety and security restrictions. Abstract : The key findings of the presented methodology to support process variability and flexibility include (1) the definition of a basic process specification framework being capable of handling different levels of process adaptivity and considering safety and security restrictions in each of its defined steps, (2) a formal process specification language and model refinement methods, (3) static business process adaptations, and (iv) dynamic (or ad‐hoc) adaptations. Abstract state machines are used to formalise the different parts of the suggested approach.